PENERAPAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS SISWA KELAS VII SMP NEGERI 3 BANDA ACEH - Dara Maulydia, Revina; Safitri, Ria; Ellianti; Rufian, Nurul (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Mathematical literacy skills are an important aspect in mathematics learning which plays a role in improving students' critical thinking and problem solving skills. However, various research results show that the level of mathematical literacy of students in Indonesia is still relatively low. This research aims to determine the increase in mathematical literacy of class VII-2 students at SMP Negeri 3 Banda Aceh through the application of the problem-based learning (PBL) model. The research method used is classroom action research (PTK) with a quantitative descriptive approach. Data was collected through tests given before and after implementing PBL. The research results showed an increase in the average value of students' mathematical literacy, from 40 in the pre-action stage to 65 in cycle I and 70 in cycle II. The application of PBL which involves contextual problems, such as distributing stock of sale bananas, calculating exam results, distributing cakes, and calculating zakat fitrah, has proven to be effective in increasing students' understanding of mathematical concepts and their skills in solving problems. This finding is in line with learning theory which states that the connection of material with real life can increase students' interest and understanding. Thus, the PBL model can be used as an alternative learning strategy to increase students' mathematical literacy.